2018
DOI: 10.1186/s13104-018-3309-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease (COPD): neutrophils, macrophages and lymphocytes in patients with anterior tuberculosis compared to tobacco related COPD

Abstract: ObjectiveThe inflammatory profile of chronic obstructive pulmonary disease (COPD) related to tobacco is known in certain studies while that of the post tuberculosis form is not yet known. This study aimed to evaluate the levels of neutrophils, macrophages and lymphocytes cells in sputum of COPD patients with history of smoking or anterior tuberculosis. Enumeration of cells in samples was analyzed using standard microscopy.ResultsWe enrolled 92 participants, 46 (50%) were COPD subjects comprising 22 (47.83%) sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Studies report that myeloperoxidase and elastase released by activated neutrophils amplify the production of IL-8 [ 29 ], which would justify its high concentration in COPD/tobacco patients who have a higher number of neutrophils. Our recent study on the same population showed that the neutrophil count was higher in post-smoking COPD compared to the post-TB form [ 30 ]. GRO is an important chemotactic mediator of neutrophils, endothelial cell adhesion and degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies report that myeloperoxidase and elastase released by activated neutrophils amplify the production of IL-8 [ 29 ], which would justify its high concentration in COPD/tobacco patients who have a higher number of neutrophils. Our recent study on the same population showed that the neutrophil count was higher in post-smoking COPD compared to the post-TB form [ 30 ]. GRO is an important chemotactic mediator of neutrophils, endothelial cell adhesion and degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are also commonly found in airways of individuals with severe asthma [42] and cystic fibrosis [43]. A greater number of neutrophils in the lavage fluid of smokers, as well as the sputum of people with COPD, has also been reported [44, 45]. Neutrophils modify mucus properties and increase mucus viscosity through releasing DNA nets [46, 47].…”
Section: Gel-forming Mucinsmentioning
confidence: 99%
“…In addition, studies report that myeloperoxidase and elastase released by activated neutrophils amplify the production of IL-8, which would justify its high concentration in COPD/tobacco patients who have a higher number of neutrophils. Our recent study on the same population showed that the neutrophil count was higher in post-smoking COPD compared to the post-TB form [31]. GRO is an important chemotactic mediator of neutrophils, endothelial cell adhesion and degranulation.…”
Section: Discussionmentioning
confidence: 87%